The Effect of Using Digital Information Resources on Fulfilling the Information Needs of UIN Jakarta Library Science Students - Muzhaffar, Mohamad Miqdad Jihad; Rianti, Fahma (Librarianship in Muslim Societies, 2025)
This study aims to determine how much influence the use of digital information sources has on fulfilling the information needs of UIN Jakarta Library Science study program students class of 2020. This study uses a quantitative method with an associative approach by collecting data through distributing questionnaires. Respondents of this study are 60 students of the 2020 Library Science study program who used digital information sources as a reference in doing coursework with an accidental sampling technique. This study uses validity and reliability instrument tests, classical assumption tests which include normality, heteroscedasticity, and linearity tests, as well as simple linear regression analysis tests, T-tests, and partial determination coefficient tests to analyze data. The uses and gratification theory is applied in this study to examine how and to what extent the media can satisfy the audience's demands. According to the findings, students' ability to meet their coursework information needs is impacted by using digital information sources. The impact of accessing digital information sources on meeting students' information demands for coursework is very significant, as seen by the 73.2% influence given and the 26.8% influenced by other aspects not evaluated. The results of hypothesis testing indicate that students' information demands are met by using digital information sources.